Design of gas-handling systems and facilities - Stewart, Maurice (Elsevier, 2014)
Updated and better than ever, Design of Gas-Handling Systems and Facilities, 3rd Edition includes greatly expanded chapters on gas-liquid separation, gas sweetening, gas liquefaction, and gas dehydration -information necessary and critical to production and process engineers and designers. Natural gas is at the forefront of today''s energy needs, and this book walks you through the equipment and processes used in gas-handling operations, including conditioning and processing, to help you effectively design and manage your gas production facility. Taking a logical approach from theory.
Keywords: Petroleum engineering -- Equipment and supplies.; Oil fields -- Equipment and supplies.; Oil fields -- Production methods.; elektronické knihy; electronic books